Monitoring the quality of groundwater from wells in the Pokrovsk District of Donetsk region - Shvets, I.; Zbykovskyy, Y.; Bohomaz, O. P.; Богомаз, О. П. (EAGE Publishing BV, 2025)
In Donetsk region, which has always suffered from a shortage of surface water, groundwater is a strategic water resource. In Pokrovsky District, under martial law, when water channels, pumping stations, treatment facilities and water supply networks were destroyed, groundwater became the only alternative solution to the water supply problem. This article is based on the data obtained as a result of the analysis of quality parameters from 151 active wells, located in the city of Pokrovsk and nearby areas of Donetsk region. During the monitoring, borehole water studies were carried out in Pokrovsk District according to 9 indicators: Salinity, Total Hardness, Alkalinity, pH, Turbidity, Total Iron content, content of Nitrates, Nitrites, Phosphates. It was found that 20% of water samples exceeded the standard for Salinity by 300-400%, and for Total Hardness - by 400-500%. Half of all samples exceed the water quality standard by 5-6 times. Monitoring of groundwater from wells in Pokrovsk District showed that this water cannot be used as drinking water without preliminary purification. It was found that the standard indicators of drinking water quality were exceeded many times, especially Salinity (100% of samples), Total Hardness (96.1% of samples), Nitrate content (80.6% of samples). Groundwater from wells in Pokrovsky District does not meet the requirements of both Ukrainian and European water quality standards for most quality indicators. The main causes of pollution of this water are anthropogenic and geological conditions.